Effects of Unilateral Conditioning Activity on Acute Performance Enhancement: A Systematic Review - Krzysztofik, Michał; Wilk, Michał; Pisz, Anna; Kolinger, Dominik; Tsoukos, Athanasios; Aschenbrenner, Piotr; Stastny, Petr; Bogdanis, Gregory C (Journal of sports science & medicine, 2022)
This review aimed to summarize the reported effects of unilateral conditioning activity (CA) on unilateral performance, bilateral performance, and the contribution of activated body limb to bilateral performance. A systematic search on MEDLINE, SPORTDiscus, Scopus, and Google Scholar was conducted on February 2022. Twenty-three studies met the inclusion criteria. Throwing, jumping, swimming, change of direction, and isokinetic performance were used as outcome measures to assess the impact of unilateral CAs on inducing post-activation performance enhancement. Eleven studies examined the effectiveness of resistance exercises as a CA, seven investigated plyometric exercises, and five used isokinetic muscle actions as CAs. Notably, only three studies directly compared the effects of bilateral and unilateral CA, and no study reported possible changes in the contribution of each limb during bilateral exercises executed following unilateral CA. Split squats were the most often studied CA (7), and it was shown that multiple sets of high-loaded split squats (85% one-repetition maximum) executed as CA, improve vertical jumping and change of direction after 4 to 8 min of recovery. At the same time, multiple sets of alternate leg bounds performed with ~10% body weight or without any external load result in an improvement of sprint performance, 2 and 8 min later, with the effect being greater when loaded jumps are used. The unilateral CAs such as split squats, alternate leg bounds, and drop jumps can be effectively used to acutely improve a wide variety of athletic tasks, including jumping, sprinting, change of direction, and swimming performance.
Keywords: post-activation potentiation; Exercise; terapie cvičením; plyometrická cvičení; Post-activation performance enhancement; Plyometric Exercise; lidé; postura těla; sportovní výkon; cvičení; Posture; Humans; Athletic Performance; athletic performance; Exercise Therapy; resistance training